Kesiapsiagaan Masyarakat Menghadapi Bencana Gunung Merapi: Studi Kasus di Desa Umbulharjo, Sleman - Permanasari, Happy Ade; Sunarto, Sunarto (UI Scholars Hub, 2011)
Daerah Istimewa Yogyakarta adalah provinsi yang rawan bencana terutama Gunung Merapi. Untuk meminimalkan korban bencana dikembangkan program kesiapsiagaan masyarakat menghadapi bencana gunung merapi melalui desa siaga. Tujuan penelitian ini mengetahui pelaksanaan kegiatan dan penerapan program kesiapsiagaan masyarakat menghadapi bencana gunung merapi di Desa Siaga Umbulharjo. Penelitian ini menggunakan rancangan penelitian studi kasus dengan analisis kualitatif. Subjek yang diteliti adalah pelaku pelaksanaan kegiatan pada pelaksanaan desa siaga, sedangkan objek penelitian adalah situasi sosial dalam pelaksanaan kegiatan. Pengumpulan data dilakukan dengan metode observasi nonpartisipatif, wawancara mendalam, dokumentasi, member check, dan triangulasi. Pelaksanaan kegiatan sudah baik, pembiayaan sudah cukup, pelatihan-pelatihan sudah baik, sosialisasi, sarana-sarana yang ada, kinerja kader, dan peran Puskesmas baik. Namun, keberhasilan pelaksanaan kegiatan kesiapsiagaan tersebut belum diikuti dengan keberhasilan pelaksanaan desa siaga. Masih banyak masyarakat yang tidak mengetahui tentang desa siaga. Pelaksanaan kegiatan kesiapsiagaan sudah baik, tetapi tidak diikuti dengan pelaksanaan desa siaga secara umum. Yogyakarta Province is a disaster-prone province, especially the mountain trim. Disaster preparedness is essential to minimize the disaster victims so formed the community program on disaster preparedness through Desa Siaga of Mount Merapi alert. To determine the activity and how the implementation of community disaster preparedness programs Mount Merapi on the implementation of Desa Siaga in the Umbulharjo Village alert This study was a descriptive study using a case study research design with qualitative analysis. Subjects in the study was the perpetrator of the community in dealing with disaster preparedness merapi mountain on implementation of desa siaga with the object of research is the social situation in the implementation of preparedness merapi mountain. Resource persons determined by the method of purposive and snowball effect if necessary. The collection of data by way of nonparticipatory observation, indepth interviews, documentation, member check, and triangulation. Implementation of the activities of disaster preparedness in the face of the mountain communities have nice views of the trim is already sufficient financing, training, training has been good from the parties involved, socialization, existing facilities, the performance of cadres, and the role of good health. The success of the implementation of disaster preparedness in the face of the mountain communities are not followed by smoothing the successful implementation of the desa siaga, seen from many people who do not know what a desa siaga. Implementation of the activities of disaster preparedness in the face of the mountain communities have a good trim but it is not followed by the implementation of desa siaga in general.